Sustained Functional Improvement by Hepatocyte Growth Factor-Like Small Molecule BB3 after Focal Cerebral Ischemia in Rats and Mice. Issue 6 (June 2015) - Chaparro, Rafael E; Izutsu, Miwa; Sasaki, Toshihiro; Sheng, Huaxin; Zheng, Yi; Sadeghian, Homa; Qin, Tao; von Bornstadt, Daniel; Herisson, Fanny; Duan, Bin; Li, Jing-Song; Jiang, Kai; et al.
Hepatocyte growth factor (HGF), efficacious in preclinical models of acute central nervous system injury, is burdened by administration of full-length proteins. A multiinstitutional consortium investigated the efficacy of BB3, a small molecule with HGF-like activity that crosses the blood-brain barrier in rodent focal ischemic stroke using Stroke Therapy Academic Industry Roundtable (STAIR) and Good Laboratory Practice guidelines. In rats, BB3, begun 6 hours after temporary middle cerebral artery occlusion (tMCAO) reperfusion, or permanent middle cerebral artery occlusion (pMCAO) onset, and continued for 14 days consistently improved long-term neurologic function independent of sex, age, or laboratory. BB3 had little effect on cerebral infarct size and no effect on blood pressure. BB3 increased HGF receptor c-Met phosphorylation and synaptophysin expression in penumbral tissue consistent with a neurorestorative mechanism from HGF-like activity. In mouse tMCAO, BB3 starting 10 minutes after reperfusion and continued for 14 days improved neurologic function that persisted for 8 weeks in some, but not all measures. Study in animals with comorbidities and those exposed to common stroke drugs are the next steps to complete preclinical assessment. These data, generated in independent, masked, and rigorously controlled settings, are the first to suggest that the HGF pathway can potentially be harnessed by BB3 for neurologic benefit after ischemic stroke.